Being like Gaia: Biomimicry and Ecological Ethics. (October 2019) - Dicks, Henry
This article analyses the philosophical status and ground of biomimicry's most distinctive principle: nature as measure. Starting with the argument that this principle is ethically normative, I go on to compare the ecological ethic it embodies with Aldo Leopold's land ethic. In so doing, I argue that the ultimate measure against which the ethical rightness of our actions should be judged is the way of being of Gaia, which is to let be her present inhabitants. I then explore the idea that taking as measure Gaia's way of being provides powerful responses to a number of longstanding problems in environmental ethics, including the question of its 'centre', duties to preserve and restore nature, and duties to present and future beings.